Childcare, Labor Supply, and Business Development: Experimental Evidence from Uganda - Gulesci, Selim (My University, 2025)
We randomly offered a childcare subsidy, an equivalent cash grant, or both to mothers of three-to-five-year-old children. The childcare subsidy substantially increased the labor supply and earnings of single mothers, highlighting the importance of time constraints for them. Among couples, childcare did not affect mothers’ labor market outcomes but instead increased fathers’ salaried employment. At the household level, childcare led to higher income and consumption and improved child development. Cash grants positively affected mothers’ labor supply and income irrespective of the household structure, suggesting the general importance of credit constraints for women’s business development.
PUBLISHED
Keywords: International Development; Development economics